Penerapan Komunikasi Politik dalam Penetapan Peraturan Daerah Kota Kendari - Muhammad Najib Husain (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2011)
The problem in this study is how the implementation of the political communication in the establishment of local standards to eradicate illiteracy Qur’an. The location of the study is at the Office of Parliamentary Inquiry Kendari. Theory used in this study is Communication Group Theory which is more determined by Lasswell Formula. This study used informants up to five people with informant’s determination technique using purposive sampling (on purpose). Data obtained from this study were analyzed through qualitative descriptive technique. The result of this study indicates that the implementation of political communication in overcoming of illiteracy Qur’an is divided into four stages of the hearing, a series of meetings of the Special Committee, plenum and a plenary session. The four stages of the process of this meeting cannot be separated from the name of political communication, in which there is a communicator, communicant, themes sage delivered and t he channel used for the fourth process is going well.